Cystic fibrosis transmembrane conductance regulator modulators in cystic fibrosis: current perspectives - Schmidt, Béla Z (Clin Pharmacol, 2016)
Mutations of the CFTR gene cause cystic fibrosis (CF), the most common recessive monogenic disease worldwide. These mutations alter the synthesis, processing, function, or half-life of CFTR, the main chloride channel expressed in the apical membrane of epithelial cells in the airway, intestine, pancreas, and reproductive tract. Lung disease is the most critical manifestation of CF. It is characterized by airway obstruction, infection, and inflammation that lead to fatal tissue destruction. In spite of great advances in early and multidisciplinary medical care, and in our understanding of the pathophysiology, CF is still considerably reducing the life expectancy of patients. This review highlights the current development in pharmacological modulators of CFTR, which aim at rescuing the expression and/or function of mutated CFTR. While only Kalydeco® and Orkambi® are currently available to patients, many other families of CFTR modulators are undergoing preclinical and clinical investigations. Drug repositioning and personalized medicine are particularly detailed in this review as they represent the most promising strategies for restoring CFTR function in CF.